Determinants of utilization of malaria preventive measures during pregnancy among women aged 15 to 49 years in Kenya: an analysis of the Malaria Indicator Survey 2020 - Beatrice Mkubwa; Juliana Kagura; Tobias Chirwa; Latifat Ibisomi; Samson Kinyanjui (Malaria Journal, 2022)
Abstract Background Malaria is a significant cause of morbidity and mortality. Malaria infection in pregnancy can have severe consequences for the fetus and the mother. To fight against malaria infection in pregnancy, Kenya integrated the issuance of an insecticide-treated net (ITN) and intermittent preventive treatment with sulfadoxine-pyrimethamine (IPTpSP) with antenatal care (ANC) for pregnant women. However, the uptake of the ITN and IPTpSP is still low. Individual, social, or structural factors may influence the low uptake. It is, therefore, important to identify the determinants associated with the uptake of ITN and IPTpSP during pregnancy in Kenya. Methods Data were from the 2020 Kenya Malaria Indicator Survey (MIS). A total of 1779 women between the ages of 15 to 49 years who had a history of either being pregnant or having given birth within 5 years before the MIS survey were included. Survey-adjusted multinomial logistic regression was used in the analysis. Results During pregnancy, ITN use was more than half (54.9%). The use of at least one dose of IPTpSP was 43.5%, three or more doses of IPTpSP was 27.2%, and only 28.2% of the participants used both ITN and IPTpSP during pregnancy. The significant determinants of combined use of ITN and IPTpSP during pregnancy were maternal age (RR 3.57, CI 1.80–7.08; p=<0.001), maternal education (RRR 2.84, CI 1.33–6.06; p=0.007), wealth index (RR 2.14, CI 1.19–3.84; p=0.011) and living in the different malaria epidemiological zones: lake endemic (RRR 10.57 CI 5.65–19.76; p=<0.001), coastal endemic area (RRR 4.86 CI 1.86–12.67; p=0.001), seasonal (RRR 0.21 CI 0.10–0.39; p=<0.001) and low risk (RRR 0.07, CI 0.03–0.17; p=<0.001). Conclusion The uptake of malaria preventive measures is still below 80% for both ITN and IPTpSP during pregnancy in Kenya. The significant results on determinants of the use of ITN and IPTpSP could be considered in implementing malaria prevention programmes during pregnancy. For example, sensitizing the community on the importance of antenatal care visits will provide a platform to teach the importance of malaria prevention in pregnancy. Moreover, the pregnant mothers receive an ITN and IPTpSP during the ANC visit.